Smiling and the Negotiation of Humor in Conversation. Issue 7 (3rd October 2019) - Gironzetti, Elisa; Attardo, Salvatore; Pickering, Lucy
ABSTRACT: This study investigates the function of smiling intensity as a nondiscrete marker of humor in conversation. The smiling intensity of participants in eight conversational dyads was measured relative to the occurrence of humorous and nonhumorous events in the conversation. A relationship was found between higher smiling intensity and the occurrence of humorous event across conversations, thus confirming the value of smiling as a marker of humor. The results show that the occurrence of humor correlates positively with an increase of smiling intensity relative to the nonhumorous stretches of talk, and it is foreshadowed by a localized increase of smiling both generally and when humor is predictable. Moreover, during humorous events participants displayed framing smiling patterns, often preceded or followed by smiling accommodation or inverted smiling gestures, which are representative of the conversational dynamics of the dyad and the ongoing negotiation of meaning.